Development of rescheduling and operation technology to support comfortable railway transportation - Maki, Kentaro; Kato, Yuko; Hashimoto, Yuuki; Tsutsumi, Yuhi (IEEJ Journal of Industry Applications, 2025)
This study provides an overview of Hitachi, Ltd.’s rescheduling and operation technologies focused on energy conservation, effective resource utilization for carbon neutrality and optimization and automation to address the decline in skilled workers. These developments are set against the backdrop of global carbon neutrality goals and the decreasing number of skilled workers due to a declining birthrate and an aging population. In the field of train traffic management, the "Dynamic Headway Solution" predicts demand by analyzing passenger flow and updates the train control timetable based on the results. Additionally, the “Hybrid traffic management AI” integrates the expertise of traffic controllers into rescheduling plans, ensuring the feasibility of the final output through machine-learning AI. These technologies enhance travel comfort and operational efficiency, compensating for the reduced number of skilled personnel. In driver assistance, "Technology for generating energy-saving speed profiles" and its application, "Technology to follow the speed profile as the application," were developed to realize train operation, that adhere to energy-efficient speed profiles. Field tests of “Driver Advisory System” in TOKYO MONORAIL CO., LTD have demonstrated a total power consumption reduction of 16.4%. This technology supports global carbon neutrality goals.